ANALISA DAN PERANCANGAN SISTEM FUZZY UNTUK PENENTUAN BEASISWA - Muhammad Yunus; Suriyati Suriyati (Universitas Bumigora, 2016)
The lack of quota each scholarship awarded by the RISTEK DIKTI make students vying to get it. For example, in 2016 a scholarship PPA quotanya 12 people and scholarships BPP as many as 11 people, while registering perbeasiswa can reach hundreds of students. Of course, with this state of student affairs should be thorough and careful in the selection of the requirements that have been proposed student. Especially in the student still using simple calculations and application of semimanual for decision-making. Given each scholarship PPA and BBP has several requirements that must be met students we need a system that is able to decide objectively. So that decisions are absolutely on target in accordance with the government's expectations. Therefore, in this study the theme of the fuzzy system for selecting scholarship in STMIK Bumigora Mataram. The results of this study contribute to the recommendations that indicate a student suitably receive certain types of scholarships with an accuracy of 80%. The indicator is used as a determinant in the decision-making scholarship acceptance form of the economic situation of parents, grade point average, points student, active in the organization and the certificate of student activities.